POWER PROJECTION AND COUNTER-TERRORISM: STRATEGIES FOR SMALL STATES LIKE BRUNEI DARUSSALAM - Lee, Brice Tseen Fu; Bibi, Gulshan, Ms (Journal of Terrorism Studies, 2023)
This study delves into the intricacies of power projection strategies and counter-terrorism measures, emphasizing their relevance to small states, with a specific focus on Brunei Darussalam. Using a dual matrix model, the research categorizes various strategies based on risk-reward parameters, offering a structured insight into potential approaches these states can employ against potential aggressors. The counter-terrorism matrix is the initial focal point, recognizing the contemporary significance of terror threats and their unique challenges for small nations. Subsequently, the power projection matrix offers a broader view of defense tactics beyond counter-terrorism. By synthesizing information from primary academic sources, the study aims to provide a holistic understanding of how smaller states can navigate the complexities of modern defense and security. The findings underscore the importance of strategic alignment between power projection and counter-terrorism, promoting a dynamic defense paradigm tailored to the nuanced needs of small states.